New data on the taxonomy, distribution and host plants of Australian Epermeniidae (Lepidoptera: Epermenioidea) - Gaedike, Reinhard (Zootaxa, 2018)
During the examination of hitherto undetermined specimens, six new species were found: Gnathifera fuscostriata sp. nov., G. luridicapitella sp. nov., G. montana sp. nov., G. robinsoni sp. nov., Epermenia (Epermeniola) macrodentata sp. nov., Gaedikermenia australica sp. nov. Ochromolopis paropsias Gaedike, 1972 is a new synonym of Gnathifera opsias (Meyrick, 1897). The taxa epispora Meyrick, 1897 and parasitica Meyrick, 1930, previously placed in the genus Epermenia, are transferred to Gaedikermenia Sohn & Wu, 2015. The male genitalia of Gnathifera bidentella (Gaedike, 1981) and G. acacivorella (Gaedike, 1968), and the female genitalia of G. pseudaphronesa (Gaedike, 1972) and G. queenslandi (Gaedike, 1968) are described and illustrated for the first time. First records within Australia are established for nine species. New host plants are recorded for Gnathifera eurybias (Meyrick, 1897), G. bipunctata (Gaedike, 1968), G. opsias (Meyrick, 1897), Paraepermenia santaliella Gaedike, 1968 and Gaedikermenia epispora (Meyrick, 1897). Now 25 Epermeniidae species are known from Australia. The systematic and generic affiliation of Epermenia xeranta Meyrick, 1917, is still uncertain.